Critical reflections on teaching challenging content: do some students shoot the (white) messenger?. Issue 5 (2nd September 2016) - Gair, Susan
Abstract: Racism is an enduring reality in Australian society for Indigenous Australians, reflecting the experiences of Indigenous peoples in colonized countries worldwide. While social work services delivered by Indigenous Australians might be the preferred option, the graduation rate of Aboriginal and Torres Strait Islander students from Australian social work training is low and non-Indigenous social workers provide most service delivery. As a non-Indigenous social work educator at an Australian university, I recognize that teaching culturally relevant curricula, in order to produce antiracist social work graduates who recognize racism and privilege, is crucial but challenging. The purpose of this article is to share my ongoing critical reflections, particularly with regard to student dissatisfaction and possible disengagement with difficult content, and my actions for improved teaching and learning, in order to graduate work-ready social workers.